Revisiting the Foundations of Liberation Education: Paulo Freire's legacy. - Ronald David Glass (Universidade Federal do Rio Grande do Sul, 2013)
This essay examines, critiques, and extends the ontological, epistemological, ethical, and political foundations of Paulo Freire's theoryof liberation education; it also situates Freire's legacy with in the global applicationof his ideas in a wide range of educational contexts. It defends historicity and praxis as essential characteristics of human existence, exposes the problems with notions of authentic identities, and elaborates a historicized understanding of knowledge production. The essay argues for liberation education to be grounded in an ethics without righteousness coupled with a politics of militant nonviolence.